Effects of curved path walking compared to straight path walking in older adults with cognitive deficits: A systematic review and network meta‐analysis. (17th January 2022) - Lee, Han Suk; Shim, Sung Ryul; Kim, Jun Ho; Ko, Mansoo
Abstract: Objective: To determine whether the existing literature provides evidence that curved path walking time can be a reliable marker of cognitive impairment among older adults using a network meta‐analysis (NMA). Data Sources: PubMed, Web of Science, ScienceDirect, Scopus, and Korean Studies Information Service System (KSISS) electronic databases were searched in December 2019. Study Selection: Studies that included the following variables were selected: (P): patients with cognitive impairment, (I): straight path versus curved path walking, (C): control group without cognitive impairment, (O): walking time, and (S): cross‐sectional or longitudinal study design. In total, 21 studies were selected for the NMA, which was performed to compare the standardized mean difference (SMD) of walking time on curved and straight paths. Results: Older adults with dementia had significantly longer walking times than older adults with mild cognitive impairment (MCI) for both straight path walking and curved path walking. The SMD of straight path walking time was 0.59 (95% credible interval [CrI]: 0.39, 0.81) for older adults with MCI and 0.90 (95% CrI: 0.65, 1.16) for older adults with dementia. The SMD of walking time on a curved path was 0.52 (95% CrI: −0.22, 1.26) for older adults with MCI and 1.98 (95% CrI: 1.20, 2.92) for those with dementia. In older adults with dementia, the correlation coefficient of the Fisher's z value was higher for curved path walking than for straight path walking. Conclusion: The way people with dementia walk exhibits signs of cognitive impairments. NMA confirmed that older adults with dementia requires significantly longer time to walk the same distance than healthy controls or older adults with MCI for both curved and straight path walking.